2022
DOI: 10.1007/s10055-022-00711-w
|View full text |Cite
|
Sign up to set email alerts
|

Examining the potential of VR program Tilt Brush in reducing anxiety

Abstract: Recent advancement in technology has made virtual reality (VR) more accessible and immersive than ever before, resulting in its increasing utility in various industries. Despite this, VR has remained an underutilised tool within clinical psychology. This study aimed to explore the potential of using VR for therapeutic benefits through examining the level of flow and anxiety-reducing effects of freeform drawing in real life (on paper) versus drawing in VR (using Tilt Brush) via a randomised-controlled trial wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 97 publications
2
0
0
Order By: Relevance
“…On average, patients in our study showed a sense of presence (measured with the IPQ) similar to results in other VR studies and interpreted as representing a high sense of presence by these authors 41–43 . In line with this research, patients scored highest on the spatial presence scale, describing the sense of being physically there in the VR and lower on the involvement subscale 37 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…On average, patients in our study showed a sense of presence (measured with the IPQ) similar to results in other VR studies and interpreted as representing a high sense of presence by these authors 41–43 . In line with this research, patients scored highest on the spatial presence scale, describing the sense of being physically there in the VR and lower on the involvement subscale 37 .…”
Section: Discussionsupporting
confidence: 90%
“…(measured with the IPQ) similar to results in other VR studies and interpreted as representing a high sense of presence by these authors. [41][42][43] In line with this research, patients scored highest on the spatial presence scale, describing the sense of being physically there in the VR and lower on the involvement subscale. 37 The involvement subscale depends on how well the virtual environment captures the participants' attention and may be higher in more engaging and interactive VR applications.…”
Section: Discussionsupporting
confidence: 78%
“…Additionally, VR is beginning to be used as a supplementary tool in psychotherapy for treating conditions such as post-traumatic stress disorder, depression, anxiety, and other psychological illnesses [62][63][64][65], with VR painting, thanks to its highly immersive creative environment, expanding ways of creative expression and opening rich therapeutic avenues for art-based psychotherapy. Several pilot studies using Tilt Brush [66][67][68] have proven the effectiveness of VR painting in processing psychological emotions, capable of inducing positive emotions and reducing stress.…”
Section: Vr Painting Application Scenariosmentioning
confidence: 99%